Essential mapwork skills - Ross, Simon R. J. (Oxford University Press, 2014)
Features: 30 case studies on a wide range of physical, human and issues-based topics, with global coverage -- Features high-quality, high impact maps and photos, including satellite, aerial, ground photography and a variety of mapping at different scales -- Extended skills and reference sections to include key ICT skills and internet-based references